TRANSFORMASI NILAI VIA SINETRON DAN PROBLEM URBANISASI KULTURAL DITINJAU DARI PERSPEKTIF TEORI KAPITAL PIERRE BOURDIEU - Mohammad Bahrul Ulum (JURNAL AT-TURAS, 2014)
This write try approach issue transformation of value that happen through impressions of sinetron with in order to teory of Bourdieu about capital, where he (capital) play role that very important in affect habit a society. The sinetron is complexion of impressions that the most many broadcast by televition in Indonestion. Through various sinetron, proces domination of discourse happen. Result from the proces is urbanization or cultural of society to a value and culture urban for example that appear in televition. The sinetron domination the all simbolic of capital that have power for compel viewers acknowledge presence hierarchy of structure between himself with the people that views in screen. Finally, in simple borrow term of Foucault “sinetron can be regarded a “rite truth” that engineered for produce habit of society to direction that desired capital of power.